Pore Pressure Estimation Using Bowers Methods in Shale Gas Reservoir Jambi Sub-Basin - Benny A. Bungasulu (Universitas Cenderawasih, 2022)
Pore pressure prediction has important implications in determining the success of a drilling activity. Information of subsurface pore pressure prediction in hydrocarbon exploration and production is very important. For geologist this information can be used to determine of hydrocarbon generation and maturation within a basin, while for petroleum engineer pore pressure prediction is very important to maintain the production rate and for drilling engineer this information is useful for mud weigh and casing designs prior drilling activities to prevent blow out. This study is conducted in the well A and B, Field